Employing deliberate practice to overcome the effects of hemifacial condylar hyperplasia and hypoplasia on a classical singing technique - Stapela, Hanli (University of Pretoria, 2021)
Dissertation (MMus (Performing Art))--University of Pretoria, 2021.